2020
DOI: 10.3390/v12121403
|View full text |Cite
|
Sign up to set email alerts
|

The AC2 Protein of a Bipartite Geminivirus Stimulates the Transcription of the BV1 Gene through Abscisic Acid Responsive Promoter Elements

Abstract: Geminiviruses possess single-stranded, circular DNA genomes and control the transcription of their late genes, including BV1 of many bipartite begomoviruses, through transcriptional activation by the early expressing AC2 protein. DNA binding by AC2 is not sequence-specific; hence, the specificity of AC2 activation is thought to be conferred by plant transcription factors (TFs) recruited by AC2 in infected cells. However, the exact TFs AC2 recruits are not known for most viruses. Here, we report a systematic ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…ABREs responding to ABA were reported previously in other viruses and in plants. For example, the ABREs occur in promoters of horseradish latent virus (HRLV) 48 and mungbean yellow mosaic virus (MYMV) 49 , and in promoters of the pyrroline-5-carboxylate synthetase (P5CS) gene from barley 50 and Arabidopsis 51 . These ABREs-including promoters were also responsive to ABA treatment and/or drought stress 48 , 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…ABREs responding to ABA were reported previously in other viruses and in plants. For example, the ABREs occur in promoters of horseradish latent virus (HRLV) 48 and mungbean yellow mosaic virus (MYMV) 49 , and in promoters of the pyrroline-5-carboxylate synthetase (P5CS) gene from barley 50 and Arabidopsis 51 . These ABREs-including promoters were also responsive to ABA treatment and/or drought stress 48 , 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…While our hypothesis has the virtue of simplicity, reality is probably more complex. In this regard, it was recently shown that abscisic acid (ABA) response elements in mungbean yellow mosaic virus (MYMV), another bipartite begomovirus, are required in addition to the CLE for activation of the NSP / BR1 promoter [ 64 ]. While ABA response elements are not present in the CP promoters of TGMV, CaLCuV, or MYMV, it is likely that as yet undiscovered activators and co-activators are involved in CP expression.…”
Section: Discussionmentioning
confidence: 99%